2019
DOI: 10.1103/physrevd.100.016009
|View full text |Cite
|
Sign up to set email alerts
|

Revisit to electrical and thermal conductivities, Lorenz and Knudsen numbers in thermal QCD in a strong magnetic field

Abstract: We have explored how the electrical (σ el ) and thermal (κ) conductivities in a thermal QCD medium get affected in weak-momentum anisotropies arising either due to a strong magnetic field or due to asymptotic expansion in a particular direction. This study, in turn, facilitates to understand the longevity of strong magnetic field through σ el , Lorenz number in Wiedemann-Franz law, and the validity of local equilibrium by the Knudsen number through κ. We calculate the conductivities by solving the relativistic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 78 publications
0
56
0
Order By: Relevance
“…Earlier the nascent strong magnetic field was thought to decay very fast with time, resulting in the magnetic field of weaker strength. However, it was later found that the realistic estimates of electrical conductivity of the medium may elongate the lifetime of the magnetic field [7][8][9]. It thus becomes imperative to investigate the effects of both strong and weak magnetic fields on the signature of the novel matter produced in URHICs.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier the nascent strong magnetic field was thought to decay very fast with time, resulting in the magnetic field of weaker strength. However, it was later found that the realistic estimates of electrical conductivity of the medium may elongate the lifetime of the magnetic field [7][8][9]. It thus becomes imperative to investigate the effects of both strong and weak magnetic fields on the signature of the novel matter produced in URHICs.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have used the resummed propagators for quarks and gluons immersed in a thermal medium in the absence and in the presence of a strong magnetic field by the respective self-energies and finally the poles of respective propagators yield the medium generated (quasiparticle) masses for quarks and gluons. With this quasiparticle description, the thermal and electrical conductivities were found finite [8], but larger in the anisotropy induced by the strong magnetic field than by the expansion. Here also, in the magnetic field-driven (B-driven) anisotropy, not only the magnitude of shear viscosity becomes larger than that in the expansion-driven anisotropy, but its increase with temperature also becomes faster.…”
Section: Introductionmentioning
confidence: 95%
“…Different versions of quasiparticle description exist in the literature based on different effective theories, such as the Nambu-Jona-Lasinio model and its extension PNJL model [62][63][64], Gribov-Zwanziger quantization [65,66], thermodynamically consistent quasiparticle model [67] etc. However, our description relies on perturbative thermal QCD, where the medium generated masses for quarks and gluons are obtained from the poles of dressed propagators calculated by the respective self-energies at finite temperature and/or a strong magnetic field [8].…”
Section: Quasiparticle Description Of Partons At Finite T and Strmentioning
confidence: 99%
See 2 more Smart Citations